The Impact of COVID-19 on Radiotherapy Services in Scotland, UK: A Population-based Study. Issue 2 (February 2023) - Grocutt, L.; Rutherford, A.; Caldwell, D.; Wilkinson, C.; Chalmers, A.J.; Dempsey, L.; Kelly, C.; O'Cathail, S.M.
Abstract: Aims: The effect of the COVID-19 pandemic on cancer radiotherapy services is largely unknown. The aim of the present study was to investigate the impact of the resultant contingency plans on radiotherapy cancer services in Scotland. Materials and methods: Detailed data of radiotherapy activity at our centre were collected from 1 April 2019 to 31 March 2021. Differences in mean weekly radiotherapy courses, dose and fractionation patterns and treatment intent were compared with corresponding pre-pandemic months for all treatment sites. Qualitative data were collected for a subgroup of radical radiotherapy patients. Results: Total radiotherapy courses decreased from 6968 to 6240 (–10%) compared with the previous year, prior to the pandemic. Average weekly radiotherapy courses delivered were 134 (standard deviation ±13), decreasing by 10% to 120 (standard deviation 15) (Welch's t -test, P < 0.001). The greatest decrease in new start treatment courses was observed from May to August 2020 (–7.7%, –24.0%, –16.7% and –18.7%) compared with the corresponding months in 2019. A significant reduction was seen for female patients <70 years (–16%) compared with females >70 years (–8%) or their male counterparts (–7% and –6%, respectively). By diagnosis, the largest reductions between pre- and post-pandemic levels were for anal (–26%), breast (–18%) and prostate (–14%) cancer. Contrarily, a significant increase was found for bladder (28%) and oesophageal (11%) cancers. Conclusions: Over the first 12 months of the COVID-19 pandemic, radiotherapy activity significantly decreased compared with the 12 months prior. Due to issued guidance, the use of hypofractionated regimens increased, contributing to the reduction in treatments for some tumour sites. An increase in other tumour sites can probably be attributed to the reduction or cancellation of surgical interventions. These results will inform our understanding of the indirect consequences of the pandemic on radiotherapy services. Highlights: The COVID-19 pandemic affected radiotherapy activity in Scotland. Radical radiotherapy courses decreased by 10% during the first year of the pandemic. Most clinical sites saw a decrease in average weekly courses, but bladder- and oesophageal-related attendances increased. Women <70 years saw a significant reduction in weekly courses, primarily due to the rapid adoption of the FAST-Forward trial.